Odontogenic myxoma of anterior mandible treated with enucleation and curettage: A case report - Rawat, Amit; Varma, Amit; Gedam, Unnati (Journal of Orofacial Research, 2020)
Odontogenic myxoma is a rare intra-osseous benign odontogenic tumour of the jaw bone which may cause resorption of the cortical bone. In this paper, the author reports a case of odontogenic myxoma treated with enucleation and curettage in a 25-year young man who reported with a painless swelling in the chin region of the mandible. The Panoramic Radiograph, showed unilocular radiolucency extending from the left second premolar to the right second molar region of the mandible without disrupting the cortical bone. Considering the age of patient, asymptomatic nature of the disease and non-aggressive radiographic features, conservative management with enucleation and curettage was planned. During the post-operative follow up of 8 month, the patient was asymptomatic. Thus, conservative approach can be used in asymptomatic and non-aggressive cases odontogenic myxoma.